2003
DOI: 10.1186/1471-2326-3-1
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi anemia genes are highly expressed in primitive CD34+hematopoietic cells

Abstract: Background: Fanconi anemia (FA) is a complex recessive genetic disease characterized by progressive bone marrow failure (BM) and a predisposition to cancer. We have previously shown using the Fancc mouse model that the progressive BM failure results from a hematopoietic stem cell defect suggesting that function of the FA genes may reside in primitive hematopoietic stem cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…1D, lanes 1, 2). Collectively, these data indicated that Fancd2 is expressed in hematopoietic tissues including a population of bone marrow which contains HSCs, in keeping with previous studies indicating that FA genes are expressed in bone marrow in Lin- cells, CD34− cells and in CD34+ stem cells [36]. …”
Section: Resultssupporting
confidence: 89%
“…1D, lanes 1, 2). Collectively, these data indicated that Fancd2 is expressed in hematopoietic tissues including a population of bone marrow which contains HSCs, in keeping with previous studies indicating that FA genes are expressed in bone marrow in Lin- cells, CD34− cells and in CD34+ stem cells [36]. …”
Section: Resultssupporting
confidence: 89%
“…Polymerase chain reaction (PCR) was performed as follows: 94°C, 30 seconds; 55–60°C, 1 minute; and 72°C, 1 minute for 40 cycles. Primer sequences for the following genes are published: Angiopoietin‐1 ( Ang‐1 ), Angiopoietin‐2 ( Ang‐2 ), Tie‐1 , Tie‐2 , Flk‐1 and Flt‐1 [5], Flt‐4 [19], Cd34 [20], Endoglin [21], c‐kit [22], Aa4 [23], and Vcam‐1 [24]. We also designed primers for the following: Hhex , 5′‐ATCTCAGAGGATTCCGACCAGG‐3′ forward, 5′‐ATTCCCCAATGTTGCCCCCAC‐3′ reverse (513 bp); Cd133 , 5′‐GGAAAAGTTGCTCTGCGAACC‐3′ forward, 5′‐TGCTTGTTTGCTGGAGGGTC‐3′ reverse (608 bp); Tal1 , 5′‐GCCCAAAGATTTCCCCAATG‐3′ forward, 5′‐AAACCCAGTGCCCCAAACAC‐3′ reverse (543 bp); VE‐Cadherin 5′‐CAGCCAGCATCTTGAACCTG‐3′ forward, 5′‐GAGATTCACGAGCAGTTGGT‐3′ reverse (506 bp) and vWF 5′‐TGTTTTGTGGCGTGTATGTGAGG‐3′ forward, 5′‐GTGTTCTGGGTTTTCTGGAGTTTG‐3′ reverse (584 bp).…”
Section: Methodsmentioning
confidence: 99%
“…48 Using Fancg Ϫ/Ϫ mice as a model, multiple defects at the stem and precursor cell compartments have been characterized, including decreased repopulation potential, 49,50 a defect in stem cell cycling, 51 and increased sensitivity to nitric oxide. 52 However, these defects do not result in spontaneous bone marrow failure, indicating that, unlike human beings, mice can compensate for defective stem/precursor cell dysfunction, perhaps related to their longer telomeres.…”
Section: Telomerase Activity Maintains Telomere Length In Fancg ؊/؊ Hmentioning
confidence: 99%